Noninvasive Evaluation of Cellular Proliferative Activity in Brain Neurogenic Regions in Rats under Depression and Treatment by Enhanced [(18)F]FLT-PET Imaging - Tamura, Yasuhisa (J Neurosci, 2016)
Neural stem cells in two neurogenic regions, the subventricular zone and the subgranular zone (SGZ) of the hippocampal dentate gyrus, can divide and produce new neurons throughout life. Hippocampal neurogenesis is related to emotions, including depression/anxiety, and the therapeutic effects of antidepressants, as well as learning and memory. The establishment of in vivo imaging for proliferative activity of neural stem cells in the SGZ might be used to diagnose depression and to monitor the therapeutic efficacy of antidepressants. Positron emission tomography (PET) imaging with 3′-deoxy-3′-[(18)F]fluoro-l-thymidine ([(18)F]FLT) has been studied to allow visualization of proliferative activity in two neurogenic regions of adult mammals; however, the PET imaging has not been widely used because of lower accumulation of [(18)F]FLT, which does not allow quantitative assessment of the decline in cellular proliferative activity in the SGZ under the condition of depression. We report the establishment of an enhanced PET imaging method with [(18)F]FLT combined with probenecid, an inhibitor of drug transporters at the blood–brain barrier, which can allow the quantitative visualization of neurogenic activity in rats. Enhanced PET imaging allowed us to evaluate reduced cell proliferation in the SGZ of rats with corticosterone-induced depression, and further the recovery of proliferative activity in rats under treatment with antidepressants. This enhanced [(18)F]FLT-PET imaging technique with probenecid can be used to assess the dynamic alteration of neurogenic activity in the adult mammalian brain and may also provide a means for objective diagnosis of depression and monitoring of the therapeutic effect of antidepressant treatment. SIGNIFICANCE STATEMENT Adult hippocampal neurogenesis may play a role in major depression and antidepressant therapy. Establishment of in vivo imaging for hippocampal neurogenic activity may be useful to diagnose depression and monitor the therapeutic efficacy of antidepressants. Positron emission tomography (PET) imaging has been studied to allow visualization of neurogenic activity; however, PET imaging has not been widely used due to the lower accumulation of the PET tracer in the neurogenic regions. Here, we succeeded in establishing highly quantitative PET imaging for neurogenic activity in adult brain with an inhibitor for drug transporter. This enhanced PET imaging allowed evaluation of the decline of neurogenic activity in the hippocampus of rats with depression and the recovery of neurogenic activity by antidepressant treatment.